The correlation of subordinate-leader intimacy and job satisfaction with organizational commitment / Laila Meiliyandrie Indah Wardani - Indah Wardani, Laila Meiliyandrie (2010)
The objective of this research was to study the correlation of subordinate-leader intimacy and job satisfaction with organization commitment. A total respondent of this research 216 employees of Government Organization in Cilegon, Indonesia were selected to fill up the questionnaires. A set of questionnaire consist of self developed Intimacy Questionnaire, Porter and Smith’s Organizational Commitment Questionnaire (OCQ), Minnesota Satisfaction Questionnaire (MSQ) by Weiss, Dawis, England, and Lofquist, and respondents’ personal data was administered to the respondents. The data were analyzed by Person Correlation and Multiple Regression analysis of Statistical Package for Social Science (SPSS) version 12.0. The result showed that there were positive correlation between organization commitment and leader – subordinate intimacy, between organization commitment and job satisfaction, and between subordinate–leader intimacy and job satisfaction. Intimacy between leader and subordinate and Job Satisfaction were simultaneosly contribute to the organization commitment. The research found that there was no correlation between demographic factors and all tested variables. As the leader and subordinate intimacy become closer and more satisfied employee, the organization commitment is proven to be higher.